Damage evolution for repairability of substandard beam-column joints - Yurdakul, Özgür; Del Vecchio, Ciro; Di Ludovico, Marco; Řoutil, Ladislav; Avşar, Özgür (National Technical University of Athens, 2021)
Substandard reinforced concrete (RC) joints often exhibited poor seismic performance even under moderate intensity earthquakes, which is due to the lack of earthquake-resistant design detailing. Premature joint cracking often compromises the seismic performance of the entire building, initiating local collapses or global failure mechanisms. The quantification of the joint repairability in terms of reduction of the structural damage as well as expected economic losses is still a challenging task. This is due to the uncertainties in the assessment of residual and maximum crack widths. This study deals with the evaluation of crack by the increasing drift-level. To this end, available numerical and experimental cyclic data on the substandard beam-column joints are collected. The variability in material properties is considered and the correlation between residual and maximum crack width is obtained. These data are then used to obtain residual-to-maximum crack width ratio by increasing drift level. The available repairability thresholds are then compared with the residual-to-maximum crack width ratio curve.
Keywords: crack width; repair; probabilistic; Beam-column joint; substandard